2000
DOI: 10.1161/01.hyp.35.3.722
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Endothelin-1 at Rest and in Response to Acute Stress in Adolescent Males

Abstract: Abstract-Blacks exhibit greater vasoconstriction-mediated blood pressure (BP) increases in response to stress than do whites. Endothelin-1 (ET-1), a potent vasoconstrictive peptide, has been proposed as having a role in racial differences in stress reactivity. We evaluated the hemodynamic and plasma ET-1 levels of 41 (23 whites, 18 blacks, mean age 18.6 years) normotensive adolescent males at rest and in response to a video game challenge and forehead cold stimulation.Measurements were performed at catheter in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 34 publications
6
76
0
Order By: Relevance
“…Furthermore, black individuals exhibited higher diastolic blood pressure and total peripheral resistance than did white individuals, and changes in ET-1 levels paralleled the changes in hemodynamic parameters. 15 Although there is no definitive proof that ET-1 caused increased peripheral resistance in that study, it clearly demonstrates racial differences in ET-1 levels in response to stress and supports our findings.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Furthermore, black individuals exhibited higher diastolic blood pressure and total peripheral resistance than did white individuals, and changes in ET-1 levels paralleled the changes in hemodynamic parameters. 15 Although there is no definitive proof that ET-1 caused increased peripheral resistance in that study, it clearly demonstrates racial differences in ET-1 levels in response to stress and supports our findings.…”
Section: Discussionsupporting
confidence: 77%
“…In addition to our studies, a recent report has provided further evidence indicating that the regulation of the ET system in African Americans may be different than the regulation of the ET system in the white population. 15 Treiber et al 15 have demonstrated that plasma ET-1 levels are elevated not only in hypertensive patients but also in African American adolescents with family histories of essential hypertension in response to acute stress. Both video game challenge and forehead cold stimulation resulted in a higher increase in circulating ET-1 concentrations in black compared with white subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with prior studies in humans and rats,2, 11, 12, 13, 14, 15, 16, 20, 21 flox mice exhibited a significant increase in plasma ET‐1 in response to CSS, whereas VEETKO mice exhibited no change in plasma ET‐1 following CSS. We found that pulmonary ET receptor expression and affinity are similar in VEETKO and flox mice, suggesting no differences in ET‐1 clearance capacity in VEETKO and flox mice.…”
Section: Discussionsupporting
confidence: 88%
“…Multiple studies in humans have observed an increase in plasma ET‐1 in response to laboratory‐induced stress,11, 12, 13, 14, 15, 16 and these findings have been further validated by a large clinical study of male and female participants 2. More important, prior studies have highlighted the importance of both a family history of CVD and preexisting CVD as modifiers of the stress responsiveness of plasma ET‐1, as reviewed by Yammine et al 8.…”
Section: Perspectivesmentioning
confidence: 99%